Optical properties of the antiferromagnetic Heusler alloy Ru2CrGe. (December 2021) - Kanomata, T.; Awano, T.; Eto, T.
Abstract: The results of optical measurements in the long wavelength infra-red (IR) range on the antiferromagnetic Heusler alloy Ru2 CrGe with a Néel temperature of 13 K are reported. At 9 K there is absence of a Drude component in the absorption coefficient indicating the insulating nature of Ru2 CrGe at this temperature. The absorption coefficient was observed to increase steeply around 50–70 cm −1  at all temperatures measured in this study. Highlights: Optical spectroscopy measurements of the antiferromagnetic full Heusler alloy Ru2 CrGe. Insulating behavior at 9 K of Ru2 CrGe. The absence of a Drude component in the absorption coefficient. Narrow-gap semiconductor Ru2 CrGe. Exchange interaction mechanism for the insulating Heusler alloys Ru2 CrGe and Ru2 CrSi.